Risk Factors Associated With Bullying in Context of a Territory Exposed to Armed Conflict: A Cross-sectional Study - Salazar Flórez, Jorge Emilio (Journal of interpersonal violence, 2024)
School violence and bullying are current and problematic events during adolescence. They are likely to have a marked presence in places highly exposed to armed conflict and violent environments, representing a double public health problem. The study aims to estimate the prevalence of different types of school violence perpetrated and experienced by school adolescents in a community with a history of exposure to armed conflict. Two thousand one hundred eighty-five school adolescents from a municipality in Colombia (males = 54.1%, 14–16 years = 38.6%) participated in the study. Nine educational institutions were included. A systematic random sampling was designed, with a proportional allocation of 35% within each school year from sixth to eleventh grade. The School Coexistence and Circumstances Affecting it—ECECA survey was applied. The prevalence and risks of bully and bullying were estimated. RRa were calculated with the 95% confidence interval adjusted for the other confounding variables. Analyses were constructed from generalized linear models, under the Poisson family and a logarithmic link function. We found a 9.3% of bullying victimization and a 3.5% prevalence of bully. A higher risk of bully was found among males, persons between 10 and 14 years of age, residents of rural or urban dispersed areas, residents of violent neighborhoods, alcohol consumers at school, and victims of aggression in childhood (RRa > 1.0, p-values <.05). The risk of victimization of bullying was higher in students younger than 15 years old, as residents of urban areas, having a history of childhood aggression, suffering abuse by a close person, and as alcohol users at school. This study provides evidence of risk factors for aggression and bullying that have implications for possible prevention measures in multiple social domains, including the individual, the family, and the school environment.